Evc works in chondrocytes and osteoblasts to regulate multiple aspects of growth plate development in the appendicular skeleton and cranial base - Pacheco, M.; Valencia, M.; Caparrós-Martín, Jose; Mulero, F.; Goodship, J.; Ruiz-Perez, V. (Elsevier Science, 2012)
Ellis-van Creveld syndrome protein homolog (Evc) was previously shown to mediate expression of Indian hedgehog (Ihh) downstream targets in chondrocytes. Consequently disruption of the Ihh/Pthrp axis was demonstrated in Evc -/- mice, but the full extent of Evc involvement in endochondral development was not totally characterized. Herein we have examined further the Evc -/- growth plate in a homogeneous genetic background and show that Evc promotes chondrocyte proliferation, chondrocyte hypertrophy and the differentiation of osteoblasts in the perichondrium, hence implicating Evc in both Pthrp-dependent and Pthrp-independent Ihh functions. We also demonstrate that Evc, which localizes to osteoblast primary cilia, mediates Hedgehog (Hh) signaling in the osteoblast lineage. In spite of this, bone collar development is mildly affected in Evc -/- mutants. The onset of perichondrial osteoblastogenesis is delayed at the initial stages of endochondral ossification in Evc -/- mice, and in later stages, the leading edge of expression of osteoblast markers and Wnt/ß-catenin signaling components is located closer to the primary spongiosa in the Evc -/- perichondrium owing to impaired osteoblast differentiation. Additionally we have used Ptch1-LacZ reporter mice to learn about the different types of Hh-responsive cells that are present in the perichondrium of normal and Evc -/- mice. Evc mediates Hh target gene expression in inner perichondrial cells, but it is dispensable in the external layers of the perichondrium. Finally, we report cranial base defects in Evc -/- mice and reveal that Evc is essential for intrasphenoidal synchondrosis development. © 2011.